'Surveillance Capitalism, COVID-19 and Social Work': A Note on Uncertain Future(s). - Garrett, Paul Michael (British Journal of Social Work, 2022)
Drawing on Shoshana Zuboff's (2019) The Age of Surveillance Capitalism , along with additional sources not ordinarily referenced in the social work literature, the article examines some of the economic and political imperatives that are driving forward new surveillance practices. The aspiration is to provide conceptual coordinates enabling practitioners, educators and those receiving social work services to arrive at a theoretically expansive sense of what may be occurring across a societal canvas. The focus is on a cluster of five enmeshed themes: first, what Zuboff means by 'surveillance capitalism'; second, why this form of capitalism has appeared so quickly over the past couple of decades; third, what the tech corporations, such as Google, seek to achieve; fourth, how surveillance capitalists aim to eliminate chance by refining technologies so as to try and constitute us as predictable human subjects; fifth, the trajectory of surveillance capitalist interventions and how they are 'doubling down' on the processes of data extraction. Zuboff's book was completed prior to the COVID-19 global pandemic and, in the latter part of article, it is argued that the current crisis will result in new forms of surveillance becoming socially embedded.